High-order harmonic generation driven by plasmonic fields:the velocity gauge. (August 2015) - Chacón, A; Lewenstein, M; Ciappina, M F
Synopsis: We present theoretical investigations of high-order harmonic generation (HHG) driven by plasmonic fields in the velocity gauge. Field-enhanced HHG using plasmonics, generated starting from engineered nanostructures, requires no extra cavities or laser pumping to amplify the pulse power. One of the main characteristics of these fields is the spatial variation in a nanometric scale and, as a consequence, strong modifications in the electron dynamics are observed. Up to now all the developed theoretical tools and numerical schemes have employed the length gauge and no attempts for implementation of approaches based on the velocity gauge have been made.